Microstructure, hardness, corrosion and dry wear of 17wt%Cr-3wt%C-7wt%Mo cast iron - Wiengmoon A. (2014)
The microstructure of a 17wt%Cr-3wt%C white cast iron with relatively high Mo addition (7 wt.-% Mo) has been investigated by X-ray difraction, light microscopy, scanning electron microscopy and transmission electron microscopy together with energy dispersive X-ray spectroscopy. Mo dissolves partly in the matrix and partly in the typical Cr-rich M7C3 eutectic carbide and also leads to microstructural modiication by forming a ine Mo-rich lamellar structure at interdendritic regions with a volume fraction of 11 %. The Mo-rich phase in this lamellar structure may also be a carbide of the M6C type and is believed to form at the lafter stage of solidiication by a subsequent eutectic reaction. Destabilization heat treatment at 1000 °C for 4 hours followed by air hardening results in precipitation of M7C3 and M23C6 secondary carbides, transformation of dendritic and eutectic austenite to martensite with some austenite being retained, and modiication of local chemical composition, importantly an increase in the Mo and C content in the matrix. his causes a signiicant improvement in hardness, corrosion and dry wear properties. Tempering at 450 °C for 4 hours leads to more temper-carbide precipitation and formation of ferrite, possibly by decomposition of retained austenite. However, an improvement in properties was not observed. © 2012 Carl Hanser Verlag, München.